Need Based Segmentation of Airport Passengers: The Case of Rajiv Gandhi International Airport, Hyderabad - Gupta, Rajiv; Venkaiah, V.; Ammani, P. (Indian Journal of Marketing, 2016)
Airport privatization models have largely been successful due to reliance over non-aeronautical revenues from retail, parking, and a host of other services which an airport offers. In this context, it becomes important for airports to understand their customers and tailor their marketing efforts according to these customers' requirements. A need-based segmentation is a first step towards this effort. An empirical research study of passenger travellers of Rajiv Gandhi International Airport (RGIA), Hyderabad, India was conducted in October 2014, and data was collected about the importance of passengers' needs. A survey of RGI airport passengers returned 502 valid responses. Using SPSS 21, empirical data analysis was done through Cluster Analysis to determine the market segments of RGIA air travellers. The market segments were further analyzed using cross tabulation with the demographic data of the passengers to obtain specific profile and main characteristics of the different segments. It was revealed that most of the top-ranked needs of all the passenger segments were similar with regard to primary core needs, but varied with respect to non-core needs. This study also located the 'needs' gaps which can be effectively exploited to maximize the non-aeronautical revenues.